Validitas dan reliabilitas kuesioner kepatuhan konsumsi tablet tambah darah pada remaja putri: Pendekatan Health Belief Model (HBM) sebagai alat ukur efektivitas - Rini Dwi Amalya; Betty Yosephin Simanjuntak; Anang Wahyudi (Poltekkes Kemenkes Aceh, 2026)
Background: Questionnaires are data collection tools that are used relevantly in a study. Questionnaire items can be used if they have been proven valid and reliable. An instrument if r count ≥ r table then the statement item can be said to be valid, reliable if the Cronbach's alpha result is > 0.70. . The prevalence of anemia in women in Indonesia is 23.9%, while the prevalence of anemia in women aged 5-14 years is 26.4% and 15-24 years is 18.4%. . Compliance is generally influenced by individual perceptions regarding drug use and health status.Objective: To assess whether the iron supplement consumption compliance questionnaire for adolescent girls based on the HBM theory is valid and reliable, so that it can be used as a basis for health programs and policies to prevent anemia in adolescents.Methods: A cross-sectional analytical observational technique was used with 40 respondents from SMPN 4 Bengkulu City. This study used 40 respondents because this number was sufficient for the questionnaire trial and was appropriate for the time and conditions. However, this number is still limited; therefore, the results cannot be representative of all junior high school girls in general. The six HBM domain statements of the questionnaire include vulnerability (8 items), severity (3), benefits (7), barriers (6), self-confidence (6), and cues to action (7). The survey was completed directly by respondents using a Likert scale.Results: The study found that all 37 questionnaire items were valid and reliable. This valid and reliable questionnaire can form the basis for more targeted adolescent health interventions to improve adherence to iron supplement consumption in the field.Conclusion: All questionnaire items refer to the HBM theoretical approach and can be used as a valid and reliable measuring tool to assess compliance with iron supplement consumption among adolescent groups, which can be used to educate adolescents with low compliance in iron supplement consumption.